Upaya Peningkatan Perekonomian Keluarga melalui Pelatihan Pembuatan Buket Bunga di Desa Ngradin Bojonegoro - Ari Kuntardina; Dina Alafi Hidayatin; Eka Adiputra; Latifah Anom; Dewi Rohmayanti; Hafidza Nash'ul Amrina (IKIP PGRI Bojonegoro, 2025)
The community empowerment program was implemented in Ngradin Village, Padangan District, Bojonegoro Regency. Program of STIE Cendekia Bojonegoro is aimed at developing the skills of the members of the PKK in handicrafts, specifically the skill of making flower bouquets. The activities are designed to improve family economic conditions. The program implementation goes through the stages of survey, preparation for activities, and finally reporting. Participants who attended the flower bouquet arrangement training were 20 members of the PKK of Ngradin Village. The result of the program is that participants have new skills in flower bouquet arrangement. It is hoped that this ability will have economic value that ultimately becomes an additional income for the members of the PKK of Ngradin Village. Program pemberdayaan masyarakat dilaksanakan di Desa Ngradin, Kecamatan Padangan, Kabupaten Bojonegoro. Program dari Tim Pengabdian Masyarakat STIE. Cendekia Bojonegoro ditujukan pada pengembangan kemampuan anggota PKK Desa Ngradin dalam kerajinan tangan, yaitu ketrampilan merangkai buket bunga. Kegiatan ini sebagai salah satu upaya untuk meningkatkan perekonomian keluarga. Pelaksanaan program melalui tahapan survey, persiapan pelaksanaan kegiatan, dan terakhir pelaporan. Peserta yang mengikuti pelatihan merangkai buket bunga adalah 20 anggota PKK Desa Ngradin. Hasil dari program adalah peserta memiliki kemampuan baru dalam ketrampilan merangkai buket bunga. Diharapkan kemampuan ini memiliki nilai ekonomi yang pada akhirnya menjadi tambahan penghasilan bagi anggota PKK Desa Ngradin.